TECNOLOGIE MULTIVISIONE E QUADRI PARLANTI PER RIVIVERE I FASTI DELLA TUSCIA FARNESE - Minelli, Maria Rita (Archeomatica, 2013)
Al Palazzo Farnese di Caprarola un museo dell'impossibile tra suggestioni, proiezioni e applicazioni interattive rende ancora più emozionante e spettacolare la visita grazie alle installazioni multimediali del Distretto Tecnologico per i beni e le attività Culturali del Lazio (DTC), gestito da Filas. Il progetto è curato da Unicity, Giunti Editore e Fondazione Rosselli. It's called "La Tuscia Farnese" and is the multimedia installation that enriches the traditional guided tour of the Palazzo Farnese in Caprarola to rediscover the history and splendor of the Farnese family through digital technologies. A museum of the impossible, led by multi-vision systems, 3D reconstructions, paintings speakers and virtual books, made under the actions of District Technology for Cultural Heritage and Activities of Lazio (DTC), managed by Filas on behalf of the Region Lazio. The project - run by Unicity, Giunti Editore and Fondazione Rosselli and with the contribution of Aldo di Russo - is the result of an important collection and digitization of original drawings and ancient books, photographic campaigns in the reference area combined with the most advanced digital technologies, under the supervision of Professor Francesco Antinucci, director of the Cognitive Processes and New Technologies of the Institute of Psychology of the CNR.